IMPROVING POULTRY FEED QUALITY THROUGH WAREHOUSE MANAGEMENT AND AFLATOXIN PREVENTION TO SUPPORT COMMUNITY FOOD SECURITY IN TERUWAI VILLAGE - I Ketut Gede Wiryawan; Syamsuhaidi; Erwan; Dwi Kusuma Purnamasari; Samsul Mahrip; Vebera Maslami (Universitas Mataram, 2026)
The Tui Jati Livestock Farmers Group is a consortium of breeders engaged in the practice of poultry farming. The decline in poultry productivity is attributable to inadequate feed management and aflatoxin contamination. Farmers currently lack adequate knowledge about feed management and aflatoxin contamination. The application of proper feed management and aflatoxin prevention is one of the appropriate technologies urgently needed to enhance livestock productivity and support the local economy. The nutritional enhancement of feed can be achieved by incorporating maggots as a protein source and utilizing poultry feces as a medium for growth. This innovation is characterized by its simplicity in terms of implementation at the group level.The objective of this community service initiative is to facilitate outreach and technology transfer pertaining to feed management and aflatoxin prevention to the Tui Jati Livestock Farmers Group in Teruwai Village, East Praya District, Central Lombok Regency. Proper feed management and the prevention of aflatoxin contamination are crucial to increasing poultry productivity, both for broiler and layer chickens. The findings of this initiative have the potential to enhance farmers' knowledge and skills by 95% in the identification of poultry feed contaminated with aflatoxins. Preliminary field trials have demonstrated that farmers have gained a more profound understanding of the significance of selecting safe feed and detecting aflatoxin contamination through the observation of the growth of Aspergillus flavus mold. Through outreach and training initiatives, farmers are equipped with practical techniques that can be directly applied in their operations to identify contaminated feed and process feed in a manner that prevents aflatoxin risks. Additionally, farmers acquire knowledge regarding maggot feed as a potential alternative poultry feed source.